The effect of body position on oscillometric blood pressure readings in young adults: narrative review - Nimar, Rahul; Sikka, Gitanjali; Yadav, Vikram Singh (International Journal of Research in Medical Sciences, 2024)
Accurate measurement of blood pressure (BP) is crucial for diagnosing hypertension and evaluating cardiovascular risk. Although office BP readings are generally consistent with 24-hour ambulatory measurements, their accuracy can be influenced by various factors. Elements such as environmental conditions, participant behaviour, device calibration, and measurement methods can lead to variations in readings, ranging from 1-2 mmHg to as much as 20-50 mmHg. Studies show that room temperature, noise, recent physical activity, and dietary choices affect BP measurements. Additionally, differences between BP readings from the right and left arms and variations due to body position (sitting versus supine) add complexity. Demographic factors, including age and sex, also contribute to variability, highlighting the need for standardized measurement procedures. This study seeks to analyse how arm side, body position, and measurement sequence influence BP variability and its effect on hypertension prevalence, aiming to improve the precision of clinical and epidemiological assessments. Thereby findings of these studies limit the generalizability of the results to hypertensive and normotensive patient population. Previous studies have also shown that there is difference in reading of blood pressure between right arm and left arm with readings of left arm are higher than right arm with oscillometric and sphygmomanometer blood pressure measuring device. Therefore, need to develop a definitive protocol for accurately measuring oscillometric blood pressure in young adults across eight different positions of the right and left arms.